Factors influencing nurse-to-parent communication in culturally sensitive pediatric care: a qualitative study. Issue 4 (4th July 2017) - Valizadeh, Leila; Zamanzadeh, Vahid; Ghahramanian, Akram; Aghajari, Parvaneh; Foronda, Cynthia
Abstract : Background: To deliver quality healthcare to diverse patients, effective commmunication is key. Little evidence exists about what factors influence nurse-to-parent communication in culturally sensitive pediatric care. Objective: The aim of this study was to explore factors that influence nurse-to-parent communication in the provision of culturally sensitive pediatric care. Design: This study employed a qualitative content analysis. Method: The participants included 25 nurses and 9 parents from pediatric wards of hospitals located in Northwest and Central Iran. Semi-structured interviews were conducted. Data were analyzed using Graneheim and Lundman's method of content analysis. Results: Factors that influenced the nurse-to-parent communication in pediatric culturally sensitive care were 1-organizational factors (inefficient policies and professional factors) and 2-human factors (nurse-related factors and unique characteristics of the family). Sub-categories included: lack of definitive policies for delivering cultural healthcare, insufficient cultural healthcare education, professional status of nursing in society, time, individual characteristics, cultural knowledge, cultural differences, and family's health literacy. Conclusion: The Iranian healthcare system requires a paradigm shift regarding the provision of culturally sensitive care.